The Challenging Anticoagulant Therapy in COVID19 Patient with Associated Coagulopathy - Raissa Virgy Rianda; Mohammad Subkhan; Aditya Doni Pradana; Fahrun Nisa'i Fatimah; Rama Azalix Rianda; Muhammad Perdana Airlangga; Muhammad Miftahussurur (Interna Publishing, 2021)
COVID-19 became a widespread infectious disease in late 2019. Indonesia currently has the highest COVID-19 mortality rate in Asia, between 4-5 percent. Interestingly, COVID-19-associated coagulopathy characterized by an increase of several procoagulant factor levels, including fibrinogen and D-dimer, that has been associated with higher mortality and unfavorable outcomes. We report a case of a 30-year-old male admitted to the hospital with a profuse vomiting and worsening fever, cough and shortness of breath, and was diagnosed with COVID-19-associated coagulopathy. Seven days after admission, he became deteriorated with significant reduction of oxygen saturation and his coagulation parameter levels were increased with highly suspicion of pulmonary embolism. He was treated with azithromycin, isoprinosine, lopinavir, and fondaparinux with thromboprophylaxis dosage since admission. The role of increased fondaparinux dosage at the time of clinical deterioration was then followed by clinical improvement and reduced D-dimer level. Anticoagulant therapy, mainly with fondaparinux, showed a better prognosis in patients with markedly elevated D-Dimer. Fondaparinux needs to be monitored appropriately to prevent bleeding and adverse. The patient was discharged from the hospital in an improved condition and normal D-Dimer levels. There was no bleeding event nor other major side effects had been found in this case. The decision for increasing dose of anticoagulant may be determined on individual basis, considering risks, benefits, and also the most important is clinical findings.